Risk of Plate Exposure in Vascularized Fibula Flap for Mandibular Reconstruction in Primary Oral Cancers - Pai, Ashwin Alke; Chen, Angela Chien-Yu; Loh, Charles Yuen Yung; Hung, Shao-Yu; Tsao, Chung-Kan; Kao, Huang-Kai (Journal of Reconstructive Microsurgery, 2025)
To investigate the risk factors for plate exposure in primary oral cancer patients with mandibular defects undergoing tumor ablation followed by vascularized free fibular flap (FFF) transfer, we conducted a retrospective observational study in a single institution in Taiwan.The study was performed on a total of 292 primary oral cancer patients who underwent FFF reconstruction between 2015 and 2019. A variety of clinicopathological, surgical, and postoperative parameters were identified and assessed. The data were statistically analyzed with univariate and multivariate logistic regression, and the probability of plate exposure-free rate was plotted as Kaplan-Meier survival curve.The overall plate exposure rate was 28.76%. The re-exploration group had a higher rate of plate exposure than patients without re-exploration (12.2% vs. 5%, p < 0.05). The 3-year probability of plate exposure-free rates in patients with (n = 216) and without (n = 76) postoperative radiotherapy were 65.9 and 92.5%, and in patients with (n = 141) and without (n = 151) postoperative wound infection were 55.3 and 91.2%, respectively. The multivariate logistic regression showed postoperative radiotherapy and wound infection were independent risk factors for developing plate exposure (adjusted odds ratio [95% CI]: 3.73 [1.37–10.68] and 10.71 [5.15–22.26], p = 0.01 and p <0.001, respectively). More patients required surgical intervention to manage the exposure of hardware.Our study has highlighted that postoperative radiotherapy and postoperative wound infection are independent risk factors for plate exposure.
Keywords: plate exposure; mandible reconstruction; fibula flap; oral squamous cell carcinoma (OSCC)